2006
DOI: 10.1542/peds.2005-2943
|View full text |Cite
|
Sign up to set email alerts
|

Heat or Eat: The Low Income Home Energy Assistance Program and Nutritional and Health Risks Among Children Less Than 3 Years of Age

Abstract: Even within a low-income renter sample, Low Income Home Energy Assistance Program benefits seem to reach families at the highest social and medical risk with more food insecurity and higher rates of low birth-weight children. Nevertheless, after adjustment for differences in background risk, living in a household receiving the Low Income Home Energy Assistance Program is associated with less anthropometric evidence of undernutrition, no evidence of increased overweight, and lower odds of acute hospitalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(97 citation statements)
references
References 19 publications
1
95
0
1
Order By: Relevance
“…5,6 Poverty affects children both directly, when material needs are not met, and indirectly, through amplifying family stress. Children's health suffers when basic needs such as food, [7][8][9][10][11][12] housing, 13,14 and utilities 15,16 are not met. Adverse impacts include low weight for age, developmental concerns and behavioral problems, higher risk of hospitalization, and overall poor health as rated by parents.…”
Section: What This Study Addsmentioning
confidence: 99%
“…5,6 Poverty affects children both directly, when material needs are not met, and indirectly, through amplifying family stress. Children's health suffers when basic needs such as food, [7][8][9][10][11][12] housing, 13,14 and utilities 15,16 are not met. Adverse impacts include low weight for age, developmental concerns and behavioral problems, higher risk of hospitalization, and overall poor health as rated by parents.…”
Section: What This Study Addsmentioning
confidence: 99%
“…As the extent of food insecurity has become better understood, some researchers have sought to identify contextual factors at the stateand county-level that influence the likelihood that families will experience food insecurity, such as housing affordability [7,8]. Other researchers have sought to investigate the role of food insecurity in the development of adverse mental, physical, and behavioral health outcomes in childhood, such as internalizing and externalizing problems, iron deficiency anemia, and increased hospitalization [9][10][11][12][13][14][15][16]. Even so, opportunities for intervention remain elusive, in part because of a lack of clarity over the pathways linking food insecurity to healthy mental, physical, and behavioral development.…”
Section: Introductionmentioning
confidence: 99%
“…Research has confirmed this finding with recent studies demonstrating that poverty, and the unmet basic needs that result from it, results in greater susceptibility to disease and poorer health across the life span. [3][4][5][6]23,[28][29][30][31][32][33][34][36][37][38] Despite numerous leaders in the field advocating for addressing social needs as part of primary care [9][10][11][12]39 and professional guidelines emphasizing the need to address social determinants, [13][14][15][16][17] there has been little evidence to help guide this practice. 27,40 A previous study by our group demonstrated that a similar system can lead to more discussion and referrals for family psychosocial problems by pediatric trainees.…”
Section: Discussionmentioning
confidence: 99%
“…We decided to screen for these needs because of their high prevalence among urban families, 19,27 the public availability of community resources designed to address them, and previous research demonstrating the association of these needs with negative child outcomes. 23,[28][29][30][31][32][33][34] The WE CARE clinical screening instrument was adapted from a larger family psychosocial screening instrument with test-retest reliability of .92. 19 For the current study, the survey consisted of 12 questions designed to identify the 6 basic needs and determine whether mothers wanted assistance with each need (Supplemental Appendix).…”
Section: Study Arms We Carementioning
confidence: 99%